2017
DOI: 10.4186/ej.2017.21.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study & Optimization of Machining Parameters in Turning of AISI 1040 Steel with Micro-grooved WC Cutting Tools

Abstract: Abstract. In dry turning, control over chip formation and the need for the automated machining lead to an advancement in cutting tools. Such concern towards chip breakability is necessary in reducing tool wear, tool tip temperatures and surface roughness of workpiece material. The present study proposes a new development in the traditionally available cutting tools, which acts like a chip breaker. A series of micro-grooves are machined on the rake face of Tungsten carbide (WC) cutting tools using sinker Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…e study of Haque et al [27] found that feed rate, depth of cut, and cutting condition with water are the most significant factors affecting the surface roughness for turning of AISI 1040 steel. Prakash and Krishnaiah [28], Pavani et al [29], and Nair et al [30] studied the effect of cutting speed, feed rate, and depth of cut on surface roughness for turning of AISI 1040 steel. However, Nair et al [30] suggested the same three factors to study the effect of tool vibration on flank wear and surface roughness during high-speed machining of 1040 steel.…”
Section: Introductionmentioning
confidence: 99%
“…e study of Haque et al [27] found that feed rate, depth of cut, and cutting condition with water are the most significant factors affecting the surface roughness for turning of AISI 1040 steel. Prakash and Krishnaiah [28], Pavani et al [29], and Nair et al [30] studied the effect of cutting speed, feed rate, and depth of cut on surface roughness for turning of AISI 1040 steel. However, Nair et al [30] suggested the same three factors to study the effect of tool vibration on flank wear and surface roughness during high-speed machining of 1040 steel.…”
Section: Introductionmentioning
confidence: 99%